The forerunner of all things : Buddhaghosa on mind, intention, and agency - Heim, Maria, 1969- (Oxford University Press, 2013)
Scholars have long been intrigued by the Buddha's defining action (karma) as intention. This book explores systematically how intention, agency, and moral psychology were interpreted in all branches of early Theravada thought, paying special attention to the thought of the 5th-century commentator Buddhaghosa.